THE USE OF SELF-ASSESSMENT TO MINIMIZE STUDENTS’ ERRORS PUNCTUATION IN WRITING NARRATIVE TEXT - M. Ihsan Kamil Jihad Hakiki (Journal of English Education Program (JEEP), 2020)
This research deals with self-assessment that aims at investigating : 1) finding out self-assessment in minimizing students’ errors punctuation of writing, 2) finding out self-assessment strategies used by the students, 3) finding out students’ perception on the use of self-assessment. The research design of the study was a qualitative case study. To collect the data, the observation, interview and questionnaire are used in this research. The participant of the study is consisted of an English teacher and twenty two students Islamic senior high school in Panjalu. The data is analyzed by drawing accurate and valid conclusions by triangulation through different qualitative data collection methods would expose different meaningful issues regarding attitudes of students toward different teaching techniques by Allen, (2006, p.44). The result of this research showed the positive response from the students. The students tell that learning by using self-assessment or reflecting the students’ themselves is very interesting. Also they feel comfortable to study English especially learning punctuation. In conclusion, the use of self-assessment to minimize students’ error punctuation in writing narrative text is more effective in solving their problem in writing in the classroom. In this study, the suggestion is given to the teacher and the students. The teacher is also expected to provide the teaching and learning process like this to motivate and increase the students’ abilities in the learning process. The students are expected to adapt well and make self-assessment to gain experience and learn new knowledge gained from other strategy of learning. Keywords: Self-assessment, punctuation, writing